Análises nas exportações de sal marinho do estado do Rio Grande do Norte no período de 2000 a 2017. - Bezerra, Fagner de Souza (Universidade Federal Rural do Semi-Árido, 2018)
The State of Rio Grande do Norte is the largest producer of sea salt in Brazil, a centennial activity of great importance in the state economy, mainly due to the availability of existing natural resources and the predominant climate in the region. This research aims to study the variations in sea salt exports in Rio Grande do Norte from 2010 to 2017. This research is descriptive. It was investigated the variation of the salt exports, looking for data of the volume (tons) and currencies (US dollars) of the exports of the state. It was also analyzed the variation of the dollar, the production in the state and its relations with the salt export in the period. The research shows a great oscillation of the quantities exported as well as the volume of currencies and that the salt has contributed increasingly to the total exports of the state. In addition, the study suggests that the exchange rate may influence the exports of this mineral.
Monografia
Keywords: Sal marinho; Exportação; Produção; Ecônomia; Câmbio; Sea salt; Export; Production; Exchange; Economy; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO